Analisis Pengendalian Kualitas Air Distribusi dengan Metode Quality Control Circle dan FMEA (Failure Mode and Effect Analysis) di Perumdam X - Furqoni, Alzain Intan; Aryanny, Enny (Universitas Batanghari Jambi, 2025)
This study aims to improve the quality of distributed water so that it complies with the established standards of PH, turbidity, and temperature. The results of the study indicate that the percentage of non-conformities in the distribution water production process from highest to lowest in order is the type of PH quality (37%), the type of turbidity quality (32%), and the type of temperature quality (31%). Recommendations for improvement are to create Standard Operating Procedures (SOPs) for employees to regulate coagulant dosing more regularly and on schedule, to reschedule ACH dose settings more regularly (for example every 3 hours), to provide training to employees on how to administer the correct dose and the importance of administering the correct dose during the production process, to establish a routine schedule for periodic recalibration of measuring instruments and ensure all laboratory equipment complies with the established standards, and to replace the existing tube settler with a unit made of stronger, high-quality material, as well as to update the structural design to improve stability and durability.